MODERN ASSORTMENT OF HERBICIDES FOR PROTECTION OF WHITE HEAD CABBAGE STATE SCIENTIFIC - A. S. Golubev; E. I. Kirilenko; P. I. Borushko (Овощи России, 2015)
The species of pests spreading in cabbage planting are listed in the article. The recommendation for the herbicides application for cabbage protection against different pests is presented. The ways of improvement of herbicides application are shown.